ChatGPT As a Formative Feedback Tool: Improving Narrative Essay Writing Among EFL Students - Pariyanto Pariyanto; Novalita Fransisca Tungka (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
As Artificial Intelligence (AI) tools become increasingly accessible in educational contexts, their potential to support second language writing instruction warrants closer examination. This study investigates the effectiveness of formative feedback provided by ChatGPT, an AI-based language model, in enhancing the narrative writing skills of English as a Foreign Language (EFL) learners. Sixteen undergraduate students from an Indonesian university participated in the study. Each student composed a narrative essay based on a personal experience and received individualized feedback from ChatGPT using a standardized prompt. They subsequently revised their work based on this feedback. Pre- and post-revision essays were evaluated by two trained human raters using a standardized narrative writing rubric. Inter-rater reliability was confirmed with a high Cronbach’s alpha score of .91. Statistical analysis using paired-sample t-tests revealed significant improvements in overall writing quality, with the greatest gains observed in style, voice, and coherence. Qualitative data from student reflections further indicated positive perceptions of ChatGPT’s feedback, citing its clarity, detail, and ease of use. While some students noted the tool's limitations in addressing cultural or contextual nuances, overall results suggest that AI-generated feedback can serve as an effective supplement to traditional instruction. The study highlights ChatGPT's potential to enhance writing development and learner autonomy, particularly in resource-constrained EFL classrooms.